Experimental and numerical studies on the smoke extraction strategies by longitudinal ventilation with shafts during tunnel fire. (October 2021) - Wang, Mingnian; Guo, Xiaohan; Yu, Li; Zhang, Yiteng; Tian, Yuan
Highlights: Smoke extraction strategies for longitudinal ventilation in tunnel fire were conducted experimentally and numerically. The smoke diffusion is changed by stack effect caused by vertical shafts in longitudinally ventilated tunnel. The exhaust velocity is smaller than supply velocity under a bigger HRR. The exhaust velocity is independent of the HRR and fire location. The supply velocity is in the range of 3 6 m/s, greatly affected by the HRR and fire location. Abstract: With the surge of extra-long tunnels, the vertical shafts are widely used to shorten the construction period and become a part of the ventilation system during the operation period. Because of the towering mountains, the depth of vertical shafts is usually about 100 m or more, which is quite different from those of urban road tunnels. As a result, it is indispensable to set up perfect smoke extraction strategies, including exhaust velocity and supply velocity, featuring longitudinal ventilation system with vertical shafts to reduce the great loss during tunnel fire. To control smoke better, 1: 4.8 reduced-scale tests were carried out. In addition, a series of full-scale numerical simulations were established, using FDS, to refine the supply velocity of three HRRs of three fire source locations. From this study, some conclusions were drawn: (1) Without ventilation system, the temperature at the junction of the main tunnel and shaft is higher, because of more smoke vents and stronger stack effect provided by vertical shafts. (2) Due to the stack effect of vertical shafts, the exhaust velocity is smaller than the supply velocity under a bigger HRR. (3) The HRRs and the fire locations made no difference to the exhaust velocity which is 3 m/s. When the fire source is located at the exhaust region and middle region, the respective supply velocity is in the range of 3 4 m/s and 4 6 m/s. When the fire source is situated in the supply region, the supply velocity of 6 m/s is suitable for all three HRRs. (4) The fitting formulas of the exhaust region and middle region are expressed. The results in this work will provide references for tunnel designers and engineers to devise smoke extraction strategies during tunnel fires.